Acute effects of chlorogenic acids on endothelial function and blood pressure in healthy men and women - Ward, Natalie; Hodgson, J.; Woodman, R.; Zimmermann, D.; Poquet, L.; Leveques, A.; Actis-Goretta, L.; Puddey, I.; Croft, K. (2016)
Coffee is a rich source of polyphenols, primarily chlorogenic acids (CGA). Certain polyphenols and polyphenol-rich foods and beverages have been shown to improve endothelial function and lower blood pressure (BP). The aim of the present study was to investigate the acute effect of two doses of CGA (5-CGA) on endothelial function and BP. In a cross-over study, 16 healthy men and women received: (i) 0 mg purified 5-CGA (control group); (ii) 450 mg purified 5-CGA; (iii) 900 mg purified 5-CGA; and (iv) 200 mg purified (-)-epicatechin (positive control) in random order one week apart. Peak and continuous mean (60 to 240 s post ischaemia) flow-mediated dilation (FMD) was measured at baseline, 1 h and 4 h. BP was measured at baseline and every 30 min to 4 h. Plasma CGA and epicatechin levels were significantly increased at both 1 h and 4 h post their respective treatments. Peak FMD was not significantly altered by either dose of 5-CGA or the epicatechin, relative to control (p> 0.05). Relative to control, effects on continuous mean FMD response following 450 mg 5-CGA and 900 mg of 5-CGA (0.47 ± 0.16%, p = 0.016 and 0.65 ± 0.16%, p< 0.001, respectively) at 1 h and (0.18 ± 0.17%, p = 0.99 and 0.44 ± 0.16%, p< 0.05, respectively) at 4 h. There was no significant effect of any of the treatments on BP. In conclusion, the present study has found no significant effect of 5-CGA, at 450 and 900 mg, on peak FMD response. However, there were significant improvements in mean post-ischaemic FMD response, particularly at the 1 h time point in this group of healthy individuals.